Developing high performance squeeze cast Al-Cu alloys with high Fe and Cu contents. (4th March 2019) - Lin, Bo; Xu, Rui; Li, Haoyu; Shi, Ya; Xiao, Huaqiang; Zhang, Weiwen
ABSTRACT: In this paper, the microstructural evolution and mechanical properties of squeeze cast Al-Cu alloys with different amounts of Cu and Fe after T7 heat treatment were investigated using various methods, including optical microstructure (OM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), electron probe micro-analyzer (EPMA), and tensile testing. Results show that better comprehensive mechanical properties of squeeze cast Al-Cu alloys can be achieved by designing the Fe and Cu contents. These results can be attibuted to an increase in precipitate particles in the α(Al) matrix and the formation of nano-sized iron-rich intermetallics (IRIs). Ultimate tensile strength (UTS), yield strength (YS), and elongation (EL) of the Al-6.5Cu-0.6Mn-1.0Fe alloy were as high as 314 MPa, 293 MPa, and 6 %, respectively. These values were close to those of Al-Si alloys with high Fe content (1.0 %) under applied pressure, and this indicates the high potential for developing recycled squeeze cast Al-Cu cast alloys.